Determinants Factor of Accommodation Online Buying through Online Travel Agent (OTA) - Aditia Sovia Pramudita; M. Ardhya Bisma; Darfial Guslan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
The objective of this research is to identifying the determinants factor of online shopping behavior in accommodation buying to increase purchase intention and the actual buying in the hospitality sector. The hospitality industry in Indonesia is growing along with the growth of the tourism industry. Since ICT is developed in Indonesia, the behavior of the traveller changed. Online Travel Agent (OTA) and Accommodation Network Orchestrator (ANO) are emerging to fill consumer wants and needs in the way of accommodation buying. Technology Acceptance Model (TAM) is used as an approach to defining the determinants factor of online shopping behavior in accommodation buying. This research used the questionnaire to get primary data which is distributed to 358 respondents. The statistical tools used were Structural Equation Model-Partial Least Square (SEM-PLS). The result showed that all of the variables (perceived ease of use, perceived usefulness, perceived risk, perceived cost) were a significant and positive impact to purchase intention and actual use in online accommodation buying behavior.